Investigating the synergistic anti-aging effects of Sasobit and recycled engine oil in styrene-butadiene rubber modified asphalt - Li, Zhen; Lu, Zhen; Liu, Xiajun; Wang, Jianxiang (Frontiers in Materials, 2024)
During the preparation of asphalt mixtures, styrene-butadiene rubber (SBR) polymers are susceptible to thermal decomposition, which can significantly impair the binder's low-temperature performance. This study explores the potential of combining warming agents with waste materials to enhance the low-temperature properties and aging resistance of the binder. Specifically, it examines the synergistic impact of Sasobit/recycled engine oil (Sasobit/REO) composites on the rheological and physical attributes of styrene-butadiene rubber asphalt binder (SBRAB). Utilizing fluorescence microscopy (FM), bending beam rheometer (BBR), and dynamic shear rheometer (DSR), the study assesses the aging resistance and modification mechanisms of Sasobit/REO on SBRAB. The findings indicate that the incorporation of Sasobit/REO composites more effectively reduces the mix preparation temperature than either component alone. The preparation of Sasobit/REO warm mix asphalt mixtures is feasible at temperatures 20℃ lower than those required for traditional hot mixtures. These composites also enhance the performance of SBRAB at both high and low temperatures, counteracting the adverse effects associated with the individual use of Sasobit or REO. This reduced short-term aging temperature is beneficial in lessening the negative impact of high temperatures on SBRAB's performance. Moreover, the addition of Sasobit/REO composites significantly improves the thermal cracking resistance of SBRAB mixtures. The study also demonstrates that Sasobit/REO enhances the short-term and long-term aging resistance of SBRAB, paving the way for the broader application of this novel warm mix additive in the asphalt industry.